2019
DOI: 10.1210/en.2019-00264
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Oocyte-Secreted Factors BMP15 and GDF9 During IVF and in Women With Reproductive Pathologies

Abstract: Oocyte-secreted factors bone morphogenetic protein 15 (BMP15) and growth differentiation factor 9 (GDF9) are critical for folliculogenesis and fertility. This study developed ELISAs for the measurement of BMP15 and GDF9 in serum and investigated their usefulness as biomarkers of female reproductive function. Serum samples were obtained from women undergoing infertility treatments (n = 154) and from perimenopausal and postmenopausal women (n = 28). Serum concentrations of BMP15 and GDF9 were analyzed in women r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 47 publications
7
32
1
Order By: Relevance
“…Prior work by the investigators (4) evaluated serum concentrations of BMP15 and GDF9 in a cohort including 154 women undergoing infertility treatment. Within this cohort, serum concentrations of BMP15 and GDF9 were similar in women with (n ¼ 18) and without (n ¼ 52) polycystic ovary syndrome, although relationships with oocytes retrieved differed by polycystic ovary syndrome status (4). As in the current study (1), there was no relationship between the biomarkers and age (4).…”
Section: Clinical Utility Of Biomarkers For Outcome Classificationsupporting
confidence: 51%
“…Prior work by the investigators (4) evaluated serum concentrations of BMP15 and GDF9 in a cohort including 154 women undergoing infertility treatment. Within this cohort, serum concentrations of BMP15 and GDF9 were similar in women with (n ¼ 18) and without (n ¼ 52) polycystic ovary syndrome, although relationships with oocytes retrieved differed by polycystic ovary syndrome status (4). As in the current study (1), there was no relationship between the biomarkers and age (4).…”
Section: Clinical Utility Of Biomarkers For Outcome Classificationsupporting
confidence: 51%
“…Because of assay limitations protein concentrations of GDF9 and BMP15 in oocytes, follicle fluids (FFs), and serum are less well characterized. Recent studies by Riepsamen and colleagues found low but relative uniform serum concentrations of GDF9 and BMP15 throughout the menstrual cycle in both healthy ovulatory women and infertile women undergoing in vitro fertilization, possibly reflecting the total population of oocytes within a woman’s ovaries, similar to anti-Mullerian hormone (AMH) ( 34 , 35 ). However, no correlations between serum AMH and either GDF9 or BMP15 serum concentrations were found, nor with concentrations of FSH ( 34 ).…”
mentioning
confidence: 99%
“…Intrafollicular concentrations of GDF9 and BMP15 are expected to be higher than in serum. The study by Riepsamen and colleagues showed higher detection rates of GDF9 and BMP15 in FF from preovulatory follicles compared with serum ( 34 ), and with a new highly sensitive commercially available ELISA assay our group recently reported high concentrations of GDF9 in human small antral follicles collected in the natural menstrual cycle ( 36 ). We also found that women with PCO had significantly reduced intrafollicular concentrations of inhibins and an aberrant regulation of the inhibin-activin-follistatin axis, as well as AMH, which may reflect underlying mechanisms characterizing aberrant follicle growth in PCOS ( 36 ).…”
mentioning
confidence: 99%
“…Indeed, activin A, BMP15 and GDF9 concentrations are very low in serum (in the pg/mL range), leading to the quantitation in serum being difficult. A recent study showed that BMP15 and GDF9 were detectable in 61% and 29% of women ( 120 ). Serum AMH levels are significantly higher in women with PCOS than in normal ovulatory women ( 121 , 122 ).…”
Section: Discussionmentioning
confidence: 99%